Health-Related Quality of Life of Adolescent and Young Adult Survivors of Central Nervous System Tumors: Identifying Domains From a Survivor Perspective. (November 2015) - Kuhlthau, Karen; Luff, Donna; Delahaye, Jennifer; Wong, Alicia; Yock, Torunn; Huang, Mary; Park, Elyse R.
This article uses qualitative methods to describe the domains of health-related quality of life (HRQoL) that adolescent and young adult (AYA) survivors of central nervous system (CNS) tumors identify as important. Survivors clearly attributed aspects of their current HRQoL to their disease or its treatment. We identified 7 key domains of AYA CNS tumor survivorship: physical health, social well-being, mental health, cognitive functioning, health behaviors, sexual and reproductive health, and support systems. Although most aspects of HRQoL that survivors discussed represented new challenges, there were several areas where survivors pointed out positive outcomes. There is a need for a HRQoL tool designed for this population of survivors, given their unique treatment and survivorship experience. Aspects of HRQoL related to cognition, sexual and reproductive health, health behaviors, and support systems are not typically included in generic HRQoL tools but should be assessed for this population. Developing HRQoL measurement instruments that capture the most significant aspects of HRQoL will improve the ability to track HRQoL in AYA CNS tumor survivors and in the long-term management of common sequelae from CNS tumors and their treatments.